Uji Sitotoksisitas Ekstrak Etanol Daun Bayam Duri (Amaranthus spinosus L.) dengan Metode Brine Shrimp Lethality Test (BSLT) - Fauzi, Ziza Putri Aisyia; Ridwanto, Ridwanto; Rani, Zulmai; Arifin, Khairil Fikri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Free radicals can cause chronic disease, it takes years for the disease to become real or accumulative. One possibility that can occur as a result of the work of free radicals such as cancer. Cancer is one of the non-communicable diseases that is a public health problem, both in the world and in Indonesia. One of the plants that has the potential as an anticancer is Amaranthus spinosus L. The results showed that thorn spinach leaves contain strong antioxidants. This study aims to determine the class of secondary metabolites contained in the ethanolic extract of thorn spinach leaves and the cytotoxicity of the ethanolic extract of A.spinosus by looking at the LC50 value which was tested using the Brine Shrimp Lethality Test (BSLT) method. This research includes phytochemical screening of A.spinosus extract and Brine Shrimp Lethality Test (BSLT) method by looking at the number of larvae mortality of Artemia salina leach (LC50). The results of the phytochemical screening test showed that A.spinosus were positive for flavonoids, alkaloids, saponins, tannins, steroids and glycosides. The results of the cytotoxicity test using probit analysis showed an LC50 value of 269.15 g/mL, so it can be concluded that the ethanolic extract of A.spinosus is toxic and has potential as an anticancer.